1977
DOI: 10.1677/joe.0.0750073
|View full text |Cite
|
Sign up to set email alerts
|

Androgenic Control of the Harderian Gland in the Male Golden Hamster

Abstract: In the golden hamster, there are marked sex differences in the Harderian gland. Male glands (which are heavier than female glands) possess two cell forms (Type I and Type II cells); female glands only exhibit the former. Female (but not male) glands contain large amounts of porphyrin, which are readily visible as solid depositions within the lumina. The weight, histology and porphyrin content of the Harderian gland was examined in intact adult male hamsters and in male hamsters castrated for 1,2 or 8 months. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

1996
1996
1997
1997

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 102 publications
(52 citation statements)
references
References 0 publications
1
51
0
Order By: Relevance
“…It has been reported that castration in males induces loss of type I1 cells, a gradual decrease in the number of polytubular complexes, and the appearance of membrane whorls, these changes being prevented by the simultaneous administration of testosterone (Hoffman, 1971;Lin and Nadakavukaren, 1979;Payne et al, 1977). Likewise, treatment of female hamsters with testosterone induces the appearance of polytubular complexes and large vacuoles and a decrease in the number and development of membrane formations (McMasters and Hoffman, 1984;Sun and Nadakavukaren, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that castration in males induces loss of type I1 cells, a gradual decrease in the number of polytubular complexes, and the appearance of membrane whorls, these changes being prevented by the simultaneous administration of testosterone (Hoffman, 1971;Lin and Nadakavukaren, 1979;Payne et al, 1977). Likewise, treatment of female hamsters with testosterone induces the appearance of polytubular complexes and large vacuoles and a decrease in the number and development of membrane formations (McMasters and Hoffman, 1984;Sun and Nadakavukaren, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Ultrastructural observations were first reported by Bucana and Nadakavukaren (1972). Two cell forms (type I and type I1 cells) were found in male glands, but female glands possessed only one form (type I cells) Norvell, 1973, 1974;Hoffman, 1971;Payne et al, 1977). They reported the androgenic control of cell types together with porphyrin contents in male glands.…”
Section: Introductionmentioning
confidence: 91%
“…There is a clear hormonal basis to these sex differences, since castration of the adult male will convert all gland characteristics to the female pattern within a few weeks (see Table 1, together with Lin and Nadakavukaren, 1979;Payne et al, 1977;Woolley and Worley, 1954), a change which can be prevented by androgen replacement (Hoffman, 1971;Payne et al, 1977). Similarly, administration of androgens to adult females will result in the appearance of type I1 cells and polytubular complexes and a marked decrease in both porphyrin content and porphyrinogenic enzyme activity (Spike et al, 1985;Sun and Nadakavukaren, 1980).…”
Section: Effects Of Gonadal Hormones Onmentioning
confidence: 99%